Treatment of intracranial neoplasia in dogs using higher doses: A randomized controlled trial comparing a boosted to a conventional radiation protocol. (30th June 2022) - Staudinger, Chris; Meier, Valeria; Beckmann, Katrin; Körner, Maximilian; Rohrer Bley, Carla
Abstract: Background: Local progression of intracranial tumors can be the consequence of insufficient radiation dose delivered. Dose increases in the brain must be made carefully so as not to risk debilitating adverse effects such as radiation necrosis. Hypothesis: A new protocol with 10 × 4 Gy + 11% physical dose increase limited to the macroscopic tumor volume results in a clinically better outcome compared to a 10 × 4 Gy protocol. Animals: Fifty‐seven client‐owned dogs with primary intracranial neoplasia. Methods: Randomized controlled trial. Twenty‐eight dogs were assigned to the control protocol (10 × 4 Gy) and 29 to the simultaneous integrated boost (SIB) protocol with 4.45 Gy dose increase. Treatment groups were compared for outcome and signs of toxicity. Results: Mild, transient acute or early‐delayed adverse radiation effects were observed in 5 dogs. Severe late adverse effects were not seen. Between the protocols, no significant differences were found for outcome (intention‐to‐treat analysis): overall time to progression (TTP) was 708 days (95% confidence interval (95% CI) [545, 872]), in the control group it was 828 days (95% CI [401, 1256]), and in the SIB group 627 days (95% CI [282, 973]; P  = .07). Median overall survival (OS) was 684 days (95% CI [516, 853]), in the control group it was 724 days (95% CI [623, 826]), and in the SIB group 557 days (95% CI [95, 1020]; P  = .47). None of the tested variables was prognostic in terms of outcome. Conclusion and Clinical Importance: The dose escalation used with an 11% physical dose increase did not result in better outcome.